Dimensi Kinerja Manajerial Pengelola Anggaran Pada Organisasi Perangkat Daerah Kabupaten Soppeng - Asmi Rahayu; Nur Fadli (AkMen JURNAL ILMIAH, 2021)
This study aims to determine the effect of budgetary participation, budget feedback and organizational commitment on managerial performance in the Soppeng Regency Regional Apparatus Organization. This research approach uses a scientific approach. The population consists of 19 employees of the Soppeng Regency Regional Apparatus Organization. Sampling in this study using purposive sampling technique with the consideration in this study is the head of administration and financial treasurer, namely because the head of administration and financial assistant is responsible for the management of regional finances and this section is an important element in realizing the accountability of the performance of government agencies. So the total sample of this study was 38 employees at OPD Soppeng Regency. Multiple linear regression statistical techniques with the help of SPSS 23 were used to process research data. The results of the study found that budgetary participation, budget feedback and organizational commitment had a positive and significant effect on managerial performance in the Soppeng Regency Regional Apparatus Organization